Financial Literacy for Business Owners in Malaysia (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This community service focuses on solving partner problems, namely Indonesian entrepreneurs and migrant workers as well as Indonesian citizens in Malaysia. This community service is a collaboration between Umsida and the Muhammadiyah Special Branch Leadership or Pimpinan Cabang Istimewa Muhammadiyah (PCIM) Malaysia. The main objective of this activity is to provide a deep understanding of the importance of simple but effective business financial records, introduce the concept of financial literacy and provide an understanding of Islam in the context of financial management and accountability. The methods used are socialization, training, interactive discussions, and mentoring based on real cases. The results of this community service activity have succeeded in providing a real contribution to improving financial literacy and business management capacity for Indonesian entrepreneurs and migrant workers in Malaysia. Through the approach of socialization, training, interactive discussions, and mentoring based on real cases, participants gain a comprehensive understanding of the importance of financial recording and reporting, financial planning, and sharia principles in running a business. This activity encourages participants to become agents of change in their respective environments. This community service is a model of international collaboration that is relevant, sustainable, and supports the sustainable development goals (SDGs), especially point 8: Decent Work and Economic Growth.